Factors influencing awareness and attendance of traditional oral health care practices by residents of a peri-urban Community in Ibadan, Nigeria (2015)
In Order to institute preventive programmes against harmful traditional oral health practices there is a need to identify targets. To investigate factors influencing awareness and attendance of traditional oral health practices by residents of a peri-urban community in Ibadan, Nigeria. A cross-sectional study of adult residents selected by simple random sampling in a peri-urban community in Ibadan, Nigeria, was conducted over a period of six months. Information was obtained with interviewer administered questionnaires. Data were recorded using SPSS Version 16 Software. A total of 172 (44.1%) respondents were aware of the existence of traditional healers for dental problems. Only 34 (8.7%) participants had been to traditional healers on account of toothache. About 76.5% reported having relief after treatment with relapse occurring in 12 cases (46.2%). Twenty (58.8%) of these (34) participants said they would not choose this Option of treating dental problems in future. Significant associations existed between knowing that traditional healers provided dental treatment and gender (p = 0.001) or history of dental problems (p =0.008). The study showed moderate awareness of traditional oral care practices in Ibadan, Nigeria as influenced by gender and previous dental problems.